Erratum: miR-425-5p, a SOX2 target, regulates the expression of FOXJ3 and RAB31 and promotes the survival of GSCs - Rocha, Arlet Maria Acanda de la; Gonzalez-Huarriz, Marisol; Guruceaga, Elizabeth; Mihelson, Nicole; Tejada-Solis, Sonia; al., et (Archives of Clinical and Biomedical Research, 2021)
Abstract not available in the source database.